2019
DOI: 10.1038/s41419-018-1219-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 overexpression induces bortezomib resistance in multiple myeloma by targeting MCL-1 via miR-29b-3p

Abstract: Radiotherapy, chemotherapy, autologous/allogeneic stem cell transplantation, and targeted drug therapy are currently available therapeutic options for multiple myeloma (MM), but the clinical outcome remains unsatisfactory owing to frequent occurrence of drug resistance. Anti apoptosis is one of the main mechanisms to mediate drug resistance. Studies have shown that MCL-1 plays a key role in the growth of cancer cells “escaping” drug attacks, but the underlying mechanism remains unclear. Our previous study demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 41 publications
3
61
0
1
Order By: Relevance
“…Increasing studies indicate that lncRNAs are involved in resistance of tumour cells to chemotherapy via multiple mechanisms, such as regulation of tumour cell apoptosis, epithelial–mesenchymal transition, and DNA methylation . LncRNA ANRIL has been shown to contribute to drug resistance in many tumours, such as osteosarcoma, gastric cancer, and colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies indicate that lncRNAs are involved in resistance of tumour cells to chemotherapy via multiple mechanisms, such as regulation of tumour cell apoptosis, epithelial–mesenchymal transition, and DNA methylation . LncRNA ANRIL has been shown to contribute to drug resistance in many tumours, such as osteosarcoma, gastric cancer, and colorectal cancer .…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐29b‐3p, a member of miR‐29 family, has important roles in clinical practice. Pan et al () have found low expression level of miR‐29b‐3p in serum of multiple myeloma patients. Circulating basal level of miR‐29b‐3p can predict the outcome of patients with metastatic colorectal cancer treated with bevacizumab (Ulivi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance of cancer cells is one of the major causes of chemotherapy failure [22]. LncRNAs are reported to induce the drug resistance by regulating drug metabolism, autophagy, apoptosis and epithelial-mesenchymal transition [23][24][25][26]. We previously elucidated that lncRNA UCA1 promotes tumor development and metastasis in GC [18,27].…”
Section: Discussionmentioning
confidence: 99%